👤

bonjour eceque quelqu un pourrait m'aider pour ce calcul il fait le développer et le réduire

[tex] ( \sqrt{12 - 3 \sqrt{7} } + \sqrt{12 + 3 \sqrt{7} } )^{2} [/tex]


Répondre :

Bonjour,

[tex]A=\left(\sqrt{12-3\sqrt{7}}+\sqrt{12+3\sqrt{7}}\right)^2\\\\ A=\left( \sqrt{12-3\sqrt{7}}\right)^2+2\times\sqrt{12-3\sqrt{7}} \times \sqrt{12+3\sqrt{7}}+\left(\sqrt{12+3\sqrt{7}}\right)^2\\\\ A=12-3\sqrt{7} +2\sqrt{(12-3\sqrt{7})(12+3\sqrt{7} ) } +12+3\sqrt{7} \\\\ A=24+2\sqrt{12^2-(3\sqrt{7})^2 } \\\\ A=24+2\sqrt{144-63}\\\\ A = 24+2\sqrt{81}\\\\ A=24+2\times 9\\\\ \boxed{A= 42}[/tex]